Pelatihan Teknis Peningkatan kemampuan Bahasa Inggris Bagi Aparatur Sipil Negara (ASN) Di Lingkungan Pemerintah Provinsi Sumatera Barat - Dian Eka Sari; Dian Purnama Sari; Yusmalinda Yusmalinda; Andry Azhari; Yohanes Tuaderu (LPPM Universitas Bumigora, 2022)
Community service as one of the Tri dharmas that must be carried out by lecturers aims to provide knowledge and experience regarding the use of English in the scope of daily activities and the working atmosphere of ASN in the Province of West Sumatra. This training is packaged through a hybrid workshop held during the Covid 19 pandemic which was taken place from 9-18 March 2022. The focus of this training activity is the mastery of spoken English, correspondence, and TOEFL to support the role of ASN as public servants. This material is based on the results of a pre-test conducted a few days before the training day which concluded that most of the selected ASN in the province of West Sumatra is at the Basic to Intermediate level. This service team is STBA Prayoga lecturers who have the duties and functions of a planning and implementing team. The implementation phase included the process of providing material through zoom meetings and Moodle for 3 days and then continuing with the implementation of community service activities for 5 days. The results of the service show that ASN who take part in the training are able to use English actively in the form of presentations, understand how to correspond formally and formally, and increase TOEFL scores.